STRONTIUM IN CORAL ARAGONITE: 3. SR COORDINATION AND GEOCHEMISTRY IN RELATION TO SKELETAL ARCHITECTURE - Allison N.; Finch A.A.; Newville M.; Sutton S.R. (My University, 2005)
Use of the coral Sr palaeothermometer assumes that the Sr in coral skeletons is substituted randomly for Ca in the aragonite structure. The presence of Sr in additional phases e.g., strontianite, or the non random distribution of Sr across metal sites in aragonite, would complicate the Sr/Ca-sea surface temperature relationship. We have used Sr K-edge microEXAFS (extended X-ray absorption fine structure) to determine the structural state of Sr across selected microvolumes of four coral skeletons (Porites lobata, Acropora palmata, Pavona clavus, and Montastrea annularis). We used a 5 × 3 μm beam to analyse specific areas of the coral skeletal architecture, i.e., centres of calcification, fasciculi, and dissepiments. All EXAFS analyses refine, within error, to an ideally substituted Sr in aragonite, and we found no evidence of strontianite or partly ordered structural states. Anisotropy in the first shell responses results from the fact that the analysed microvolumes are not necessarily averaged for the responses of all crystal orientations in the aragonite. Although secondary ion mass spectrometry confirmed that Sr/Ca composition can vary substantially between skeletal components, we find no evidence for any contrast in Sr structural state. Sr heterogeneity may result from kinetic effects, reflecting complex disequilibrium processes during crystal precipitation, or biological effects, resulting from variations in the composition of the calcifying fluid which are biologically mediated.